Identification of novel hub genes for Alzheimer’s disease associated with the hippocampus using WGCNA and differential gene analysis - Chen, Yang; Li, Zhaoxiang; Ge, Xin; Lv, Huandi; Geng, Zuojun (Frontiers in Neuroscience, 2024)
Alzheimer's disease (AD) is a common, refractory, and progressive neurodegenerative disease, besides cognitive and memory deficits in patients are highly correlated with abnormalities in hippocampal brain regions. Therefore, the aim of this study was to explore the central genes related to AD in the hippocampal brain region by integrating the analysis methods of WGCNA and differentially expressed genes. Gene expression profiles of hippocampal brain regions GSE29378 (including normal control and AD samples) were downloaded from the GEO database. GSEA analysis revealed that there were mainly GABAergic synapses, glutamatergic synapses and other pathways enriched between these two groups. After differential analysis, a total of 225 differentially expressed genes were obtained, GO and KEGG were shown to be associated with calcium ion response, glutamatergic synapses and calcium-dependent phospholipid binding responses. Subsequent WGCNA analysis yielded the set of dark green and bright yellow modular genes most associated with AD. Further extraction yielded 176 genes from these two modules, which were taken to intersect with 225 differentially expressed genes yielding 51 intersecting genes. The cytohubba algorithm was used to screen the 10 most important hub genes among the 51 intersected genes: HSPA1B, HSPB1, HSPA1A, DNAJB1, HSPB8, ANXA2, ANXA1, SOX9, YAP1, and AHNAK, which were validated by the external dataset GES48350 and were found to have good diagnostic performance. These hub genes also contribute to further understanding of AD development in the hippocampus and drug therapy.Alzheimer's disease (AD) is a complex multi-factorial neurodegenerative disorder with a hidden onset that affects more than 50 million people worldwide (1). AD is the leading cause of mortality in dementia and due to its non-curable reality based on current medical development status, it has brought extreme economic burden to patients' households as well as continuous distress. The main clinical signs and symptoms of AD include subjective cognitive decline (SCD), behavioral change, and